The Influence of Perceived Organizational Injustice towards Workplace Personal Web Usage and Work Productivity in Indonesia - Fathonah, Nur; Hartijasti, Yanki (UI Scholars Hub, 2014)
Workplace personal web usage (WPWU) is an employee’s activity in using internet for non-related task during working hours. It is considered a counterproductive behavior when done excessively because it can interrupt employee’s productivity, but it can increase creativity and eliminate boredom when used in a rational amount. The objective of this study was to prove whether perceived organizational injustice had influence on WPWU which affected work productivity. A total of 222 respondents working in various industries were gathered through web-survey. By using multinomial logistic regression analysis, this study found that high level use of internet for unrelated jobs between 2 to 4 hours a day was influenced by respondents’ perception of not getting fair treatment and incentive for being good performer, which then caused them to perform very low completion of tasks. There were two contrasting views regarding this result; organizations considered it as deviant behavior because it reduced employees’ performance whereas employees regarded it as just short breaks to get rid of stress. Hence, this finding suggested that companies should redesign its internet policies to accommodate “Work-Life Blend”; blending work and personal lives, as a consequence of cultural shift in the era of globalization and new technologies.